2022
DOI: 10.1007/s42250-022-00421-5
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering of Anti-dengue Molecules from Plants Prescribed for Dengue: A Computational Investigation

Abstract: Dengue fever is a tropical disease spread worldwide, transmitted by the mosquito Aedes aegypti . It affects 100 million people worldwide every year and half a million cases of dengue hemorrhagic fever are registered. At present, it poses sever health burden as combined infections of COVID-19. Currently, as a combined infection with COVID-19, it is becoming a serious health burden. To identify the active molecule, Maestro V12.7 was used with different tools including LigPrep, Grid Generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition, a molecular docking study found that the andrographolide of A. paniculata has potential inhibitory activity against envelope protein and NS-5 methyltransferase of DENV [33]. Moreover, the andrographolide of A. paniculata showed a potential inhibitory activity against RNA dependent RNA polymerase of DENV [34].…”
Section: Andrographolidementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a molecular docking study found that the andrographolide of A. paniculata has potential inhibitory activity against envelope protein and NS-5 methyltransferase of DENV [33]. Moreover, the andrographolide of A. paniculata showed a potential inhibitory activity against RNA dependent RNA polymerase of DENV [34].…”
Section: Andrographolidementioning
confidence: 99%
“…Envelope protein and NS-5 methyltransferase Potential inhibitory activity [33] Andrographolide RdRp Potential inhibitory activity [34] RdRp: RNA dependent RNA polymerase, DENV: Dengue virus.…”
Section: Andrographolidementioning
confidence: 99%
“…In order to evaluate the various physicochemical and pharmacokinetic features of the phytochemicals employed in this study, a pkCSM portal was used [11].…”
Section: Pharmacokinetics Analysismentioning
confidence: 99%
“…Apigenin is also found in the aerial parts and roots of Carum carvi Linn, Dichrostachys drupifera Mill, Digitalis purpurea L, Enicostemma littorale Blume, Eryngiumcampestre L, Kaempferia galanga L, Lonicera japonica L, Matricari arecutita L, Mentha piperita Wild, Petroselinum sativum Fuss, Passiflora speciesism L, Ruellia tuberosa L, Tanacetum vulgare L and Verbaseum Thapsus L [11]. Conversely, in southern India, the apigenin-containing Carica papaya L extract is used to treat dengue to strengthen the immune system.…”
Section: Apigeninmentioning
confidence: 99%